A new interpretation of the bee fossil Melitta willardi Cockerell (Hymenoptera, Melittidae) based on geometric morphometrics of the wing - Dewulf, Alexandre (Pensoft Publishers, 2014)
Abstract. Although bees are one of the major lineages of pollinators and are today quite diverse, few well-preserved fossils are available from which to establish the tempo of their diversification/extinction since the Early Cretaceous. Here we present a reassessment of the taxonomic affinities of Melitta willardi Cockerell 1909, preserved as a compression fossil from the Florissant shales of Colorado, USA. Based on geometric morphometric wing shape analyses M. willardi cannot be confidently assigned to the genus Melitta Kirby (Anthophila, Melittidae). Instead, the species exhibits phenotypic affinity with the subfamily Andreninae (Anthophila, Andrenidae), but does not appear to belong to any of the known genera therein. Accordingly, we describe a new genus, Andrenopteryx gen. n., based on wing shape as well as additional morphological features and to accommodate M. willardi. The new combination Andrenopteryx willardi (Cockerell) is established.